Preparation of DNA-Structures in Single Molecule Experiments - Xiaohau, Liu (My University, 2012)
The study of biomolecules on a single molecule level enables the investigations of dynamic, mechanistic as well as heterogeneous behavior of the biomolecules. For studying the features of DNA-protein interactions involved in DNA-repair, on the single-molecule level, the combination of microfluidics, surface preparations and fluorescence microscopy is used by the single molecule biophysics group at the physics department at the University of Gothenburg. In addition, traditional biochemical techniques, Polymerase Chain Reaction and agarose-gel electrophoresis, are also used to produce and analyze various types of DNA used in the single molecule experiments. The work is interdisciplinary and combines physics, surface science, biochemistry and micro/nano science, which motivated me to finish my master thesis project in the field of single molecule biophysics. In order to investigate the repair of the double-stranded break (DSB), we tried to simulate the homologous recombination (HR) process in vitro to study the interaction between DNA and the protein Rad51 through single molecule experiments. The objective of this thesis project was to prepare DNA structures to mimic the damaged DNA with processed DSBs. The damaged and processed DNA structures are double-stranded DNA (dsDNA) with a 3’-single-stranded DNA (ssDNA) overhang of various lengths. These DNA structures will work as the substrates for the study of the DNA-protein interaction that are involved in the repair of DSBs. Short pieces of ssDNA (140nt) were designed and bought directly. Long pieces of ssDNA (5kb) were produced via Polymerase Chain Reaction (PCR) followed by lambda-exonuclease treatment using lambda-phage DNA (48 kbp) as template. The optimal conditions were acquired after repeated experiments and the results were verified by agarose gel electrophoresis. Finally, these ssDNA molecules were ligated to the original lambda-DNA. Fluorescently labeled Replication Protein A (RPA) that preferentially binds ssDNA, was used to confirm that the DNA samples contained the desired structure, dsDNA with 3’-ssDNA overhang. The interaction between DNA and RPA was studied in microfluidic flowcells using fluorescence microscopy where the DNA samples were attached to a functionalized lipid bilayer surface within the microfluidic flowcells.
Keywords: Fysik; Physical Sciences